Impact of new-type agricultural cooperatives on profitability of rice farms: Evidence from Vietnam's Mekong River Delta - Nhan Quoc Tran; Thong Van Ngo; Nay Van Nguyen; Thanh Duong Ngoc; Can Duy Nguyen; Tu Duong Quach; De Van Le (Economies, 2022)
The major goal of this study is to examine the impact of agricultural cooperative membership on the net return on production cost (ROC). The data used for the study were gathered from 233 rice farmers in the central Mekong River Delta's province of Hau Giang, Vietnam. Propensity score matching and two-step Heckman selection models were employed to account for possible selection bias stemming from systematically different observable and unobservable attributes between cooperative members and non-members. The findings reveal that cooperative membership has a positive and statistically significant impact on rice farmers' ROC, suggesting that agricultural cooperatives could help increase the profitability of rice farms.
Keywords: 330; agricultural cooperative; impact; Mekong River Delta; rice farm